Politics, patronage, and the transmission of knowledge in 13th-15th century Tabriz - Pfeiffer, Judith, 1964- (Iran Studies, 2014)
In Politics, Patronage and the Transmission of Knowledge in 13th - 15th Century Tabriz , an international group of specialists from different disciplines investigate the role of Tabriz as one of the foremost centres of learning, cultural productivity, and politics in post-Mongol Iran and the Middle East. While standard accounts of Islamicate history have long presented the 13th to 15th centuries as the bottom of the decline paradigm of old, the present volume demonstrates the vibrancy and originality of the intellectual and cultural production of this period by focusing on Tabriz among other capitals of the region. The volume particularly explores the transmission of knowledge and institutional and cultural patronage in the post-Mongol period. Contributors include Reuven Amitai , Nourane Ben Azzouna , Sheila Blair , Devin DeWeese , Joachim Gierlichs , Birgitt Hoffmann , Domenico Ingenito , Robert Morrison , Ertuğrul Ökten , Judith Pfeiffer , Johannes Preiser-Kapeller , F. Jamil Ragep , and Patrick Wing .